ANALISIS SISTEM PEMASARAN BERAS DI KECAMATAN MATARAM KOTA MATARAM - NI WAYAN PUTU MEIKAPASA; THERESIA SUZANNA CATHARINA; STEVANNY HANALYNA DETHAN (GANEC SWARA, 2021)
Rice is the main basic need for most Indonesian people. Mataram District as one of the sub-districts in Mataram City has a fairly dense population, so the availability of rice is very important, on the other hand, productive land in this sub-district is getting narrower so that rice supplies from other areas are needed. This study aims to determine the origin of the rice supply area and then analyze the marketing channels of rice in the Mataram sub-district, Mataram City. Based on the results of the study, it was found that all regencies on the island of Lombok supply rice to Mataram District, in addition, 2 regencies outside the island of Lombok also supply rice to various sales centers in this sub-district, namely Sumbawa Besar District and West Sumbawa. Analysis of marketing channels obtained results where there are three patterns of rice marketing channels in Mataram District. Channel I, where farmers sell wet unhulled rice to middlemen (middlemen) and then sell them to wholesalers and then supply rice to traders at retailers and then to final consumers. Channel II, farmers sell grain to collectors and then directly to retailers and final consumers and Channel III, farmers sell directly to retailers to be sold directly to final consumers. The marketing margin for channel I is the largest, and the marketing margin is the smallest for channel III. Farmer's share is largest in marketing channel III (81.25%) while the lowest is in marketing channel I (72.33%). Based on the ratio of costs and results, channel III has the highest ratio so that it is said to be the most efficient